When Does Lack of Resources Make New Firms Innovative? - Katila, Riitta; Shane, Scott (Academy of Management Journal, 2005)
We extend the resource-based perspective to explain innovation in new firms that have yet to develop resources. Using data on firms' efforts to commercialize technological inventions, we tested a model of the environmental conditions under which new firms' lack of resources alternately promotes or constrains innovation. We found that new firm innovation is greater in competitive and small markets, and in environments that do not demand extensive production assets.